Service-learning in an urban Aboriginal community: "Real Aborigines don't just live in the bush" - Johnston, Michelle; Bennett, Dawn; Mason, Bonita; Thomson, Christopher (Springer, 2016)
Service-learning is gaining greater recognition in Australian universities as an effective and powerful means by which students can learn about Aboriginal people and culture. Working in and with community provides opportunities for students to form personal relationships with Aboriginal people that will have long- term benefits for all participants. One of the first steps in establishing a service-learning project will inevitably be to decide on a location. Is a service-learning program located in a remote Aboriginal community of more benefit to students than one that is located in an urban community? This chapter describes a service-learning program that was established for media students and run in collaboration with the city of Perth Aboriginal community in Western Australia. It discusses the reasons why an urban community was the answer to our question of 'where', and how an urban service-learning project can build strong and lasting community relationships and provide a transformative learning experience for students.